Structural health monitoring of sandwich structures based on dynamic analysis - Marques, Denys; Flor, Felipe R.; de Medeiros, Ricardo; Pagani Junior, Carlos Do Carmo [UNESP]; Tita, Volnei (FapUNIFESP (SciELO), 2018)
This work aims to contribute to the development of SHM systems based on vibration methods to be applied on sandwich structures. The main objective is focused on experimental damage identification via changes in the Frequency Response Function (FRF) with the usage of damage metrics. Specimens of sandwich structures made from skins of epoxy resin reinforced by glass fiber and a core of PVC foam are manufactured. First, preliminary non-damped Finite Element (FE) models are performed, and results obtained are used to define the frequency range of interest for the experimental procedure. After that, vibration experimental analyses are carried out on undamaged specimens. The natural frequencies are compared to the preliminary FE results. Second, experimental analyses are performed on damaged specimens with and without piezoelectric sensors. Then, damage metric values are calculated based on FRFs for damaged and undamaged structures, which were obtained from experimental and FE analyses (with damping effects). In addition, a new procedure is proposed to improve the quality of results provided by the damage metric. It is shown that the new procedure is very effective to identify the damage using both amplitude and phase from FRFs. Lastly, it is discussed the potential and limitations of the FE model to predict damage metric values, comparing to experimental data.
Keywords: Experimental analysis; Finite element analysis; Sandwich structures; Structural health monitoring; Vibration methods